2014
DOI: 10.1111/jerd.12098
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Intraoral Temperature and Relative Humidity on the Dentin Bond Strength: An in Situ Study

Abstract: Some conditions of intraoral temperature and relative humidity may not impair the dentin bond strength of two-step etch-and-rinse adhesive systems. Thus, an adequate relative isolation seems to be a good alternative under the specific clinical conditions in which rubber dam isolation is either impossible or very difficult to perform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…A chamber to simulate intraoral conditions was used in other studies to investigate dentin bond strength 16 or microleakage of adhesive systems. 17 However, the chamber used in this study was limited to experiments of intraoral scanners.…”
Section: Discussionmentioning
confidence: 99%
“…A chamber to simulate intraoral conditions was used in other studies to investigate dentin bond strength 16 or microleakage of adhesive systems. 17 However, the chamber used in this study was limited to experiments of intraoral scanners.…”
Section: Discussionmentioning
confidence: 99%
“…The test housing was placed on top of a hot plate, set to an optimised temperature to achieve 37 ± 1 °C within the compartment, similar to in vivo conditions 3 . The test housing contained potassium chloride which was used to form a saturated salt solution to provide relative humidity of approximately 93 ± 3% RH in the enclosed container, similar to those conditions encountered in the oral cavity 17 . The disintegration bed was a slightly flattened silicone pipe with 4 mm holes to allow water or simulated saliva to flow over the surface of the pipe.…”
Section: Methodsmentioning
confidence: 99%
“…Saraiva et al [11] reported that both temperature and relative humidity in incisor site was significantly lower than molar site under the room condition. Therefore, the evaporation of the remaining solvent in the anterior cavity might be easier than at other sites, even when the intra-oral vacuum device was used.…”
Section: Discussionmentioning
confidence: 99%
“…Relative humidity at molar sites is close to 100 % [9][10][11]. Resin bonding in a high humidity environment has been reported to reduce bond strength [11,12,39]. Therefore, it is recommended to restore posterior teeth under humidity-controlled conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation